Sosialisasi Bahaya Penggunaan Media Sosial pada Siswa di Sekolah Dasar Negeri 09 Wanarejan Utara - Putri Salma Nur Hidayah; Alya Isni Abdilah; Muhammad Taufiq Ubaidillah; Hendri Hermawan Adinugraha (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
According to several recent studies, many children are included in the category of addiction to using cellphones, especially the use of social media. Increasingly with the degree of addiction the lightest or the most severe. Community service activities carried out by the service team reported in this study will specifically focus on socializing the dangers of using social media. Social media was chosen because the risks and dangers are greater for children because of the nature of online communities that do not interact directly and anonymously. The method used in this community service activity is active participation, which in this activity uses 4 methods, namely implementation, problem solving and games. The results of community service activities show that students of SD Negeri 09 Wanarejan Utara play social media between six to eight hours every day, far exceeding what is recommended by WHO and the lack of parental assistance in supervising children in using social media. This activity suggests several things for students, namely encouraging students' openness to what social media they use, being careful of personal data when on social media and encouraging students to become creators by creating creative content rather than being passive media consumers.